Disaster relief and preparedness: Nutritionally-balanced, cost effective, socially acceptable and sustainable emergency food aid design: A vital strategy for disaster abatement. - Lee, Lai Kuan (Universiti Sains Malaysia, 2016)

(untitled)
Flood management involves the implementation of river basin mitigation, immediate humanitarian resources, social rehabilitation measures and environmental preservation. Food aid continues to make up the majority of humanitarian appeals, and remains an important tool in response to the flood events.